The Role of Retained Austenite in Tempered Martensite Embrittlement of 4340 and 300-M Steels Investigated through Rapid Tempering - Virginia K. Euser; Don L. Williamson; Kip O. Findley; Amy J. Clarke; John G. Speer (Metals, 2021)
Tempered martensite embrittlement (TME) is investigated in two medium carbon, high strength steels, 4340 (low silicon) and 300-M (high silicon), via rapid (1, 10, or 100 s) and conventional (3600 s) tempering. Rapid tempering of 4340 diminishes the depth of the TME toughness trough, where improvements in impact toughness correspond to the suppression of retained austenite decomposition. In 300-M, retained austenite decomposition is suppressed to an even greater extent by rapid tempering. While toughness improves overall after rapid tempering, TME severity remains consistent in 300-M across the tempering conditions examined. Through interrupted tensile tests, it was found that the 300-M conditions that exhibit TME are associated with mechanically unstable retained austenite. Unstable retained austenite is shown to mechanically transform early in the deformation process, presumably resulting in fresh martensite adjacent to interlath cementite that ultimately contributes to TME. The present results emphasize the role of both the thermal decomposition and mechanical transformation of retained austenite in the manifestation of TME.